HUBUNGAN STATUS GIZI DENGAN CD4 PADA PASIEN TB PARU - Patiung, Feby; Wongkar, M. C. P.; Mandang, Veny (e-CliniC, 2014)
Abstract: The background of TBC disease is well know as the main health problem for people in the world. In 1992 WHO iconed TBC as global emergency. WHO reported that 8,8 million new cases of TBC in 2002 and the rest 3,9 trilliun recorded as HIV case. Patient having TBC disease usually experience a drop in the health nutrition status or they could be categorized as having bad nutrition status. Few factors related to health nutrition of TBC patient is unefficient energy level and protein, patient’s attitude towards food and health, experiencing TBC for quite a long time and the income of the patient itself. Few variables are needed to evaluate health nutrition of a TBC chronic. They are antropometrik including hematologik which are body mass index, total protein, albumin, total white blood cell, etc. The result show that there is no relation between body mass index and CD4, there is no relation between total protein and CD4, there is correlation between albumin and CD4, there is correlation between total white blood cell and CD4, and it can be concluded that health nutrition status have a high effect towards CD4. Keywords: CD4. Abstrak: Latar belakang: Penyakit Tuberkulosis (TB) merupakan masalah kesehatan masyarakat utama di dunia. Pada tahun 1992 WHO telah mencanangkan tuberkulosis sebagai global emergency. Laporan WHO menyebutkan bahwa terdapat 8,8 juta kasus baru tuberkulosis pada tahun 2002 dan 3,9 juta adalah kasusHIV. Pasien TB paru seringkali mengalami penurunan status gizi, bahkan dapat menjadi status gizi buruk. Beberapa faktor yang berhubugan dengan status gizi pada pasien TB paru adalah tingkat kecukupan energi dan protein, perilaku pasien terhadap makanan dan kesehatan, lama menderita TB paru serta pendapatan perkapita pasien. Untuk menilai status gizi seseorang pasien termasuk pasien TB paru diperlukan penilaian beberapa variabel baik antropometrik maupun hematologik diantaranya : indeks masa tubuh (IMT), protein total, albumin, limfosit total dan lain-lain. Hasil: Tidak terdapat hubungan antara IMT dengan CD4, tidak terdapat hubungan antara protein total dengan CD4, terdapat hubungan antara albumin dengan CD4, terdapat hubungan yang kuat antara limfosit totaldengan CD4, dan secara garis besar status gizi berpengaruh terhadap hasil CD4.Kata Kunci: CD4.